2023
DOI: 10.1039/d2cp05290c
|View full text |Cite
|
Sign up to set email alerts
|

Insight into the structural and electrochemical properties of the interface between a Na6SOI2 solid electrolyte and a metallic Na anode

Abstract: Solid electrolytes (SE) have attracted a great deal of interest as they can not only mitigate the safety issues related to currently used liquid organic electrolytes but also enable the...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 53 publications
(79 reference statements)
0
3
0
Order By: Relevance
“…, ESW of 0–1.66 V for Na 4 OI 2 and 0–1.5 V vs. Na + /Na for Na 6 SOI 2 . 686,733 This is ascribed to both the electronically insulating nature of the pristine antiperovskite structure and unreducible elements contained. 689 For some of the modified antiperovskite SEs, the coating layer may be necessary for a thermodynamically unstable interface with the Na metal anode; e.g.…”
Section: Antiperovskite Isesmentioning
confidence: 99%
“…, ESW of 0–1.66 V for Na 4 OI 2 and 0–1.5 V vs. Na + /Na for Na 6 SOI 2 . 686,733 This is ascribed to both the electronically insulating nature of the pristine antiperovskite structure and unreducible elements contained. 689 For some of the modified antiperovskite SEs, the coating layer may be necessary for a thermodynamically unstable interface with the Na metal anode; e.g.…”
Section: Antiperovskite Isesmentioning
confidence: 99%
“…Black (blue) curve in the top-left (top-right) panel represents the migration of a Na interstitial from an inner bulk site toward the Na–I (Na–S–O) surface and Na–I/Na (001) (Na–S–O/Na (001)) interface. Reproduced with permission from ref ( 89 ). Copyright 2023 Royal Society of Chemistry.…”
Section: Grain Boundaries Surfaces and Electrolyte–electrode Interfacesmentioning
confidence: 99%
“…More recently, a first-principles study performed by Choe et al 89 focused on the interface between a metallic Na anode and the Na-based antiperovskite Na 6 SOI 2 . Their calculations showed that the Na 6 SOI 2 (001) surface with two different terminations (i.e., Na–S–O and Na–I) could be used along with the Na (001) and (101) surfaces to form four different interface models due to their calculated exothermic interlayer binding energies, which ranged from −18.3 to −15.8 meV Å –2 , and formation energies of −28.0 to −21.5 meV Å –2 .…”
Section: Grain Boundaries Surfaces and Electrolyte–electrode Interfacesmentioning
confidence: 99%